IMPLEMENTASI METODE ROLE PLAY DALAM PEMBELAJARAN KOMUNIKASI MAHASISWA KEPERAWATAN - Hasan, Muhamad Ibnu; Bachtiar, Nanda (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2023)
Communication is a very important skill for a nurse in providing nursing care. Data shows that new graduates of nursing education programs still have to make extra efforts to communicate with patients. Efforts to improve communication experiences can be done in various ways, one of which is using simulations with role play techniques for nursing students in each learning process. This research aims to determine the application of the role play method in communication learning for nursing students in the third diploma nursing study program at the Harapan Bersama Polytechnic, Tegal City. This research is an experimental research using a one group pre test and post test design using a total sampling of 52 nursing students. Data collection was carried out using therapeutic communication observation sheets, communication behavior and role play implementation. The role play is designed according to the topic of therapeutic communication by each group by paying attention to the stages of creating the role play which are measured using an observation sheet. The results showed that there were differences in the average scores of pre- and post-treatment therapeutic communication skills with a significance level of p = 0.000 as well as differences in pre- and post-treatment communication behavior with a significance level of p = 0.000. Based on these results, it can be concluded that role play influences the therapeutic communication skills and behavior of nursing students, so that it can be applied as a learning method to achieve good therapeutic communication skills in nursing students.